Evaluating Environmental and Economic Impacts of Alternative Waste Management Scenarios in Kathmandu: From Landfill-Centric to Recycling & Composting - Shrestha, Shyam Babu; Lamba, Nitin (Journal of Advanced Academic Research, 2026)
This essay gives a comparison of environmental and economic benefits of three alternative solid waste management systems namely as landfilling, recycling and compost system in Kathmandu Valley where urbanization has been outpacing the source segregation, and subsequent increase in landfill overflow and municipal burdens. The quantitative research design was used to collect data presented in a structured questionnaire given to 200-300 households chosen by use of stratified random sampling in wards, income groups, and type of settlement. The survey recorded the household waste production trends, waste management behaviour, groupings on willingness to sort and participate in the groups as well as how they felt in relation to the environment and the economy. The SPSS was used in analyzing data through descriptive statistics and correlation analysis. The findings imply that there are low recycling behavior and moderate readiness to compost that is highly affected by the presence of organic materials in the municipal stream of waste. Every perception finding indicates that the general awareness of landfill-related pollution is high, and people are strongly driven in favor of environmentally preferable methods, which are composting and recycling. The correlation analysis, again, supports the fact that the degree of environmental awareness is a statistically significant predictor of the household readiness to use alternative waste management system. Altogether, the research determines landfilling as the least sustainable process and composting backed up with recycling becomes the most sustainable and economical way of Kathmandu Valley. The results offer evidence-driven information to the policy makers and town planners to formulate more resilient and sustainable municipal waste management policies.